Structural monitoring for the cyclic behaviour of concrete tunnel lining sections using FBG sensors. Issue 4 (12th October 2015) - Bursi, Oreste S.; Tondini, Nicola; Fassin, Manuel; Bonelli, Alessio
Summary: To demonstrate the viability of using fibre Bragg grating (FBG) sensors capable of detecting the inelastic cyclic response of reinforced concrete sections that are part of tunnel linings, an experimental research programme carried out on different packaging configurations of FBG sensors is presented in this paper. The programme illustrated here was part of a wider research project funded by the European Commission whose objective was the development of a decision support system for monitoring tunnel linings in seismic‐prone regions. In particular, a typical metro tunnel located in Rome area, Italy, was considered as a case study. In order to provide useful information for designing an effective sensor packaging to be applied to a final full‐scale test representing a whole lining circular section of a tunnel, pure bending tests were designed and performed on five substructure specimens endowed with different sets of fibre packaging. The outcomes of the substructure tests showed that the optimal FBG packaging solutions were unbonded sensors either embedded in concrete or mounted externally. Moreover, the designed fibre sensor system reliably performed at large deformations. In fact, the external FBG fibres applied to the full‐scale tunnel test approached maximum values of about 0.63%, whilst the internal fibres reached about 1.2%. The results obtained by FBG sensors were in good agreement with those of traditional transducers. Copyright © 2015 John Wiley & Sons, Ltd.